Preparation of Nickel/Active Carboncatalyst and its Utilization for Benzene Hydrogenation - Enggelena Septiawati; Iip Izul Falah; RHA. Sahirul Alim (Universitas Gadjah Mada, 2001)
The research on the preparation of nickel catalyst impregnated on active carbon by two methods has been carried out. The impregnation of Ni metal was done using nickel(II) chloride as a precursor. The impregnated of Ni metal on samples in A method was made in varying of percentage i.e., 0.5, 1.0 and 2.0% (w/w) as the weight proportion of Ni to active carbon and NiCl2.6H20. The concentration of Ni that would be impregnated on samples in B method was made close to Ni content of samples in A method determined by atomic adsorption spectrometry. Preparation of nickel/active carbon catalyst with A method was done with dipping the active carbon in the nickel(II) chloride solution followed by filtering and then drying at 110 °C for 4 hours, and then calcination by flowing nitrogen and reduction by hydrogen, each at 400 °C at 4 hours. The treatments made on samples in A method was also done on samples in B method, the only difference was evaporating all of precursor solution after dipping active carbon in that precursor solution was done in B method. The characterization includes: iodium adsorption test, determination of nickel content by means of atomic adsorption spectrometry, and acidity by adsorption of ammonia methods. Test of catalyst activity was done by means of hydrogenation of benzene to cyclohexane at 150, 200 and 250 °C, the pressure of 1 atm and the flow rate of hydrogen 6 mL/minute. The products were analyzed by gas chromatographic method. The results show that A method produced a catalyst with relatively low nickel content. However the acidity and ability to convert benzene to cyclohexane were relatively high and it increased as increasing the content of nickel. The temperature of the reaction was achieved at 250 °C which gave the yield on conversion of 25.3678%. The catalyst obtained by B method in the same condition of hydrogenation gave only smaller results.